Effects of butyric acid and Protoxin probiotic in the feeding of Siberian sturgeon (Acipenser baerii) - Rasool Zare; Abdolmohammad Abedian Kenari (University of Guilan, 2024)
Introduction: Using antibiotics to combat microbes and as a growth-enhancing tool in aquaculture is a common trend. However, scientific knowledge and public concerns about the development of antibiotic resistance have led to a global reduction or prohibition of these compounds. Probiotics and organic acids are potential alternative compounds to antibiotics in aquaculture. Numerous studies have been conducted on using organic acids in poultry and livestock diets. However, there is limited information regarding the employment of these compounds in fish nutrition. Nowadays, various probiotics are used as dietary supplements in the aquaculture industry. However, combining organic acids and probiotics is a new idea that has not yet been studied. Materials and Methods: In this experiment, the effects of butyric acid and probiotic supplements (Protexin) and their combination on the growth performance, body composition, intestinal microbiota, and immune responses (lysozyme and complement) in juvenile Siberian sturgeon (Acipenser baerii) were investigated. Therefore, 120 healthy fish with an average body weight of 54.85 ± 0.36 g were randomly divided into four experimental groups in three replications. The fish were fed with four diets as follows: control diet (C1, without supplementation), diet containing 2% butyric acid (T2), diet containing a combination of 2% butyric acid and 0.01% protoxin (T3) and diet containing 0.01% protoxin (T4). The fish were fed three times a day until satiation for 9 weeks. Results and Discussion: The results showed that T2 and T4 improved the growth indices of Siberian sturgeon (p < 0.05). In control and T2, the body fat contents decreased. The protein level significantly upraised in T2 (P<0.05). Adding organic acid to the fish diet dropped pH and elevated intestinal lactic acid bacteria (P<0.05). Lysozyme and complement increased in T2 and T3 (P<0.05). Conclusion: In general, the results of this study showed that butyric acid alone had a positive effect on growth, intestinal ...